The C++ programming language - Stroustrup, Bjarne, 1950- (Upper Saddle River : Addison-Wesley, 2013)
The new C++11 standard allows programmers to express ideas more clearly, simply, and directly, and to write faster, more efficient code. Bjarne Stroustrup, the designer and original implementer of C++, has reorganized, extended, and completely rewritten his definitive reference and tutorial for programmers who want to use C++ most effectively. The C++ Programming Language, Fourth Edition, delivers meticulous, richly explained, and integrated coverage of the entire language—its facilities, abstraction mechanisms, standard libraries, and key design techniques. Throughout, Stroustrup presents concise, “pure C++11” examples, which have been carefully crafted to clarify both usage and program design. To promote deeper understanding, the author provides extensive cross-references, both within the book and to the ISO standard.
Includes bibliographical references and index.
Keywords: C++ (Computer program language).